FRI0509 3D MICROSTRUCTURE OF INTACT AND OSTEOARTHRITIC HUMAN MENISCUS USING MICRO-COMPUTED TOMOGRAPHY. (June 2019) - Kestilä, Iida; Folkesson, Elin; Finnilä, Mikko A.; Turkiewicz, Aleksandra; Önnerfjord, Patrik; Hughes, Velocity; Tjörnstrand, Jon; Englund, Martin; Saarakkala, Simo
Abstract : Background: Degenerative meniscal lesions are highly prevalent in the general population and are associated with increased risk of knee osteoarthritis (OA). Development of novel methods for visualization of the early degenerative changes in the meniscus could help us better understand meniscal degradation and the onset of OA. Objectives: To develop and perform ex vivo 3D imaging of meniscus posterior horn microstructure with micro-computed tomography (μCT), and to compare specimens from healthy references with end-stage OA using histology and qualitative μCT. Methods: Medial and ipsilateral lateral menisci were retrieved from 10 patients undergoing total knee arthroplasty for medial compartment knee OA (age range 50 to 75 years, 5 women). Additionally, medial menisci were obtained from 10 cadaveric donors without known OA, to serve as reference (age range 18 to 77 years, 5 women). The samples were freshly frozen in -80°C. After thawing, the posterior horns were dissected and fixed, followed by excision of a piece for μCT imaging (Fig. 1A ). The μCT samples were dehydrated in ascending ethanol concentrations, treated with hexamethyldisilazane (HMDS), and dried in room temperature. They were then imaged with a desktop μCT (scanning parameters: 40 kV, 250 μA, 2.0 μm pixel size, 1815 ms, no additional filtering). For histological analysis, Pauli's histopathological scoring 1 was performed independently by two graders on sections from three regions (Fig. 1A ). The graders' consensus was given for each sub-score, from which the final overall consensus scores were calculated for each region. The mean difference in consensus scores (95% CI), adjusted for age and sex, were estimated between the menisci from OA knees and the reference menisci (medial OA menisci vs reference menisci, and lateral menisci from OA patients vs reference menisci) using a mixed linear regression model. The mean difference in consensus scores between the medial and lateral menisci from the same OA patient was calculated using a linear fixed effects model. The models were fitted on all three histological regions, but here we report histology results from region 2, because this region is adjacent to the piece analyzed by μCT (Fig 1A ). Results: 3D visualization of the meniscus with μCT revealed similar structural changes as histological analysis (Fig. 1C ). The histopathological consensus scores were generally higher in medial OA samples as compared to both lateral menisci from OA patients and the reference menisci (Fig. 1B ). The mean difference in histological scores (95% CI) was 4.3 (2.5, 6.1) for medial OA menisci vs reference menisci, -0.3 (-2.2, 1.5) for lateral menisci from OA patients vs reference menisci, and 4.6 (3.0, 6.2) for medial OA menisci vs lateral menisci from OA patients. Conclusion: An HMDS-based 3D μCT protocol allows unique 3D visualization of meniscus microstructures. The method enables the visualization of considerably large volumes and evaluation of the tissue's 3D organization. Therefore, it may provide additional, important information compared to conventional section-based histology. Moreover, analyzing patients with medial compartment knee OA, we found that the medial OA menisci had higher histopathological scores than both reference medial menisci, as well as the lateral meniscus from the same knee. References: [1] Pauli C, Grogan SP, Patil S, Otsuki S, Hasegawa A, Koziol J, et al. Macroscopic and histopathologic analysis of human knee menisci in aging and osteoarthritis. Osteoarthritis Cartilage2011;19:1132-41. Doi: 10.1016/j.joca.2011.05.008 [doi] Acknowledgement: We would like to acknowledge the Foundation for Research in Rheumatology (FOREUM) for funding. Disclosure of Interests: None declared